Assessing knowledge levels on coronavirus disease (COVID-19) among community members: The influence of community engagement efforts in Seke district, Zimbabwe: A cross-sectional study - Enica Rutendo Chikanya; Moses John Chimbari (PLoS ONE, 2026)
Introduction The COVID-19 pandemic posed significant public health challenges globally, with effective containment relying heavily on community knowledge and engagement. This study assessed COVID-19 knowledge levels among community members in Seke District, Zimbabwe, and evaluated the influence of community engagement efforts. Methods A community-based cross-sectional survey of 748 adults was conducted from January to March 2024 across rural, peri-urban, and farming settlements in Seke District, using structured interviews. Participants were selected using multistage cluster sampling and simple random sampling within clusters. Data were collected through structured face-to-face interviews using a pre-tested questionnaire assessing knowledge of COVID-19 (symptoms, transmission, prevention) and community engagement. Knowledge was scored on a 17-item questionnaire with a total possible score of 61 points; participants scoring 50% or more of the total possible score were classified as knowledgeable, a threshold based on prior similar studies. Data analysis included ANOVA, Student’s t-test, and post hoc tests with significance set at p < 0.05. Results Only 27% scored above the knowledge threshold. Knowledge varied significantly by gender, age, residence, religion, education, and engagement with Village COVID-19 Taskforce Committees (p < 0.05). Males, younger adults, peri-urban residents, and those engaged with taskforce services showed higher knowledge levels. Conclusion This study highlights notable knowledge gaps on COVID-19 in Seke District despite ongoing community engagement efforts. Unlike previous studies in the district, it uniquely links community engagement activities with knowledge outcomes across diverse demographic groups. Findings suggest the need for tailored, targeted public health education strategies to enhance health literacy and community participation. Strengthening inclusive community engagement can optimize pandemic preparedness and response in this and similar settings.